An antigenic threshold for maintaining human immunodeficiency virus type 1-specific cytotoxic T lymphocytes. - Jin, X; Ogg, G; Bonhoeffer, S; Safrit, J; Vesanen, M; Bauer, D; Chen, D; Cao, Y; Demoitie, M; Zhang, L; Markowitz, M; Nixon, D; et al. (2000)
BACKGROUND: Using the lymphocytic choriomeningitis virus (LCMV) model in mice, a number of studies show that memory cytotoxic T-lymphocyte (CTL) responses are maintained in the presence of continuous antigenic stimulation. Yet, other groups found that memory CTL specific for LCMV could last for a lifetime in mice without viral antigens. Thus, the extent to which an antigen is required for the maintenance of virus-specific CTL remains controversial. In humans, very few studies have been conducted to investigate the relationship between the quantity of antigen and the magnitude of CTL responses. MATERIALS AND METHODS: We quantified CTL precursors (CTLp) using a limiting-dilution analysis (LDA) and CTL effectors (CTLe) using a new Major Histocompatibility Complex (MHC) class I tetramer technology in six long-term nonprogressors (LTNPs) with human immunodeficiency virus type-1 (HIV-1) infection, as well as in eight patients whose viral loads were well suppressed by antiretroviral therapy. The viremia levels in these patients were measured using an reverse transcription polymerase chain reaction (RT-PCR) assay. The proviral DNA load in peripheral blood mononuclear cell (PBMC) was also measured by PCR in four LTNPs. RESULTS: The LTNPs had high levels of HIV-1-specific memory CTLp and CTLe, while maintaining a low plasma viral load. Despite also having low viral loads, patients whose plasma viremia was well-suppressed by effective therapy had low levels of CTLe. CONCLUSIONS: Our findings suggest that a complex, rather than a monotonic, relationship exists between CTL levels and HIV-1 viremia, including what appears to be an antigenic threshold for the maintenance of CTL at a measurable level. Under conditions of "antigen excess,", CTLe levels correlate inversely with viral load. On the other hand, under conditions that are "antigen limited," the correlation appears to be direct.